We can solve this system of equations by substituting the value of y from the second equation into the first equation.
3x + 6 = -1/3x - 4
Now, solve for x:
3x + 1/3x = -4 - 6
10/3x = -10
x = -1
Now that we have solved for x, we can substitute this value back into the second equation to find y:
y = -1/3(-1) - 4
y = 1/3 - 4
y = -11/3
Therefore, the solution to the system of equations is x = -1 and y = -11/3. Since there is only one unique solution, there is only one solution in this system of equations.
how many solutions are in
3x + 6 = y and y = -1/3x - 4
1 answer